Temperature Increases by kilohertz frequency Spinal Cord Stimulation - Zannou, Adantchede L. (Brain Stimul, 2018)
INTRODUCTION: Kilohertz frequency spinal cord stimulation (kHz-SCS) deposits significantly more power in tissue compared to SCS at conventional frequencies, reflecting increased duty cycle (pulse compression). We hypothesize kHz-SCS increases local tissue temperature by joule heat, which may influence the clinical outcomes. METHODS: To establish the role of tissue heating in KHZ-SCS, a decisive first step is to characterize the range of temperature changes expected during conventional and KHZ-SCS protocols. Fiber optic probes quantified temperature increases around an experimental SCS lead in a bath phantom. These data were used to verify a SCS lead heat-transfer model based on joule heat. Temperature increases were then predicted in a seven-compartment (soft tissue, vertebral bone, fat, intervertebral disc, meninges, spinal cord with nerve roots) geometric human spinal cord model under varied parameterization. RESULTS: The experimentally constrained bio-heat model shows SCS waveform power (waveform RMS) determines tissue heating at the spinal cord and surrounding tissues. For example, we predict temperature increased at dorsal spinal cord of 0.18–1.72 °C during 3.5 mA peak 10 KHz stimulation with a 40–10–40 μs biphasic pulse pattern, 0.09–0.22 °C during 3.5 mA 1 KHz 100–100–100 μs stimulation, and less than 0.05 °C during 3.5 mA 50 Hz 200–100–200 μs stimulation. Notably, peak heating of the spinal cord and other tissues increases superlinearly with stimulation power and so are especially sensitive to incremental changes in SCS pulse amplitude or frequency (with associated pulse compression). Further supporting distinct SCS intervention strategies based on heating; the spatial profile of temperature changes is more uniform compared to electric fields, which suggests less sensitivity to lead position. CONCLUSIONS: Tissue heating may impact short and long-term outcomes of KHZ-SCS, and even as an adjunct mechanism, suggests distinct strategies for lead position and programming optimization.